(untitled) (Panacea Journal of Medical Sciences, 2020)
Hyperuricemia as a predictor in COPD and Exacerbation. The study aims to measure serum uric acid levels in patients with chronic obstructive pulmonary disease as a predictor. Materials and Methods: It is an observational study done on 50 COPD patients newly diagnosed or previously diagnosed. Serum uric acid level, chest x-ray and pulmonary function tests were performed with consent. Results: The mean normal Serum uric acid (mg/dl) was 4.86+ 1.6. The increased mean serum uric acid (Hyperuricemia) was 9.67+ 1.8. The mean serum urea and creatinine levels were 26.74+3.91 and 0.94+0.20. The FEV1% Predicted in Normal UAC – 51.8+18.6 and in cases of Hyperuricemia 53.4+16.7. FVC% Predicted in Normal UAC was 77.5+17.8 in cases of Hyperuricemia it was 76.5+18.5. Conclusion: The outcome of our study shows serum uric acid is cost-effective, easy and non-invasive and possibly suitable in assessing the patient disease severity, progression to exacerbation.